2012
DOI: 10.4103/0973-1482.99006
|View full text |Cite
|
Sign up to set email alerts
|

Primary squamous cell carcinoma of the breast: Case report and management decisions

Abstract: Though breast carcinoma is one of the most common malignancies worldwide, adequate knowledge of this disease is still very poor. Pure primary squamous cell carcinoma of breast is one such mystery, which is encountered very rarely. Its clinical behavior should not be correlated with the standard infiltrating duct carcinoma of breast. It follows an atypical presentation in terms of tumor size, lymph node and systemic spread. It is generally a triple negative tumor with an aggressive behavior and resistance to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…Radiotherapy plays an important role, considering that most cases have a locally advanced presentation of the disease 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiotherapy plays an important role, considering that most cases have a locally advanced presentation of the disease 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicate that the prevalence of lymph node metastasis varies from 41% to 47% 7,17,18 . Patients with lymph node involvement from the neoplasm seem to have a better response to adjuvant chemotherapy compared to those with no involvement 18 .…”
Section: Discussionmentioning
confidence: 99%
“…SCCB is considered resistant to the standard chemotherapy regimens used for other breast cancers. Nevertheless, some studies found that adjuvant cisplatin-based regimens could be effective [ 6 , 7 , 21 , 22 ]. In addition, 62.1% to 85.7% of SCCB patients have overexpression of epidermal growth factor receptor (EGFR) [ 15 , 19 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because PSCCB is so rare, prognosis and optimal treatment are still controversial [1][2][3][4][5][7][8][9][10][11][12]. There is a small body of research regarding this topic which consists mainly of isolated case reports and a few larger case series.…”
Section: Discussionmentioning
confidence: 99%
“…Primary squamous cell cancer of the breast (PSCCB) is an extremely rare form of breast cancer with an incidence of approximately 0.04-0.1% of all breast cancers and more specifically 0.04-0.07% of all ductal carcinomas [1][2][3]5,[7][8][9][10][11][12]. PSCCB is a diagnosis of exclusion, with the following criteria that must be met: (1) tumor origin does not arise from overlying skin, nipple or adenexal components, (2) greater than 90% of the tumor must be composed of squamous cells, (3) no evidence of ductal or mesenchymal elements within the tissue sample, and (4) no other sites of primary squamous cell cancer are present [2][3][4].…”
Section: Introductionmentioning
confidence: 99%